Matthew Fontaine Maury papers - Maury, Matthew Fontaine, 1806-1873.; Coblentz, Catherine Cate, 1897-1951.; Smith, C. Alphonso (Charles Alphonso), 1864-1924.
Correspondence, letterbooks, diaries, journals, drafts and printed copies of speeches, articles, and other writings, notebooks, electrical experiment book, charts, and printed material relating chiefly to Maury's naval career, scientific activities and interests, service as a Confederate agent in England, and work as an immigration official for Southern expatriates in Mexico, and to the Maury (Morey) family. Documents Maury's service as a midshipman in the U.S. Navy in the 1820s and 1830s and as superintendent of the U.S. Depot of Charts and Instruments and of the U.S. Naval Observatory between 1842 and 1861. Also documents his resignation as an officer of the U.S. Navy and commission as commander in the Confederate navy (1861). Topics include meteorology, mines, oceanography, torpedoes, and the physical geography of Virginia. Includes papers of Charles Alphonso Smith regarding Maury and a typescript of a life of Maury by Catherine Cate Coblentz.
Family correspondents include Maury's wife Ann Maury (1811-1901); his children Nannie Corbin and her husband Wellford Corbin, Matthew Fontaine Maury, Jr. (1849-1886), Richard L. Maury, Mary Werth, and Eliza Withers; his cousins Ann Maury (1803-1876) and Rutson Maury; and his kinsman Franklin Minor. Correspondents include William M. Blackford, William C. Hasbrouck, Nathaniel J. Holmes, Marin H. Jansen, Maximilian (Emperor of Mexico), James Hervey Otey, Francis Henney Smith, and F. W. Tremlett.
Library of Congress Geography and Map Division.
Naval officer and oceanographer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blackford, William M., -- 1801-1864 -- Correspondence; Corbin, Nannie, -- 1837-1900 -- Correspondence; Corbin, Wellford -- Correspondence; Hasbrouck, William C. -- Correspondence; Holmes, Nathaniel J. -- Correspondence; Jansen, Marin H. -- 1817-1893 -- Correspondence; Maury, Ann, -- 1803-1876 -- Correspondence; Maury, Ann, -- 1811-1901 -- Correspondence; Maury, Matthew Fontaine, -- 1849-1886 -- Correspondence; Maury, Richard L. -- 1840-1907 -- Correspondence; Maury, Rutson, -- 1805-1882 -- Correspondence; Maximilian, -- Emperor of Mexico, -- 1832-1867 -- Correspondence; Minor, Franklin, -- 1812-1867 -- Correspondence; Otey, James Hervey, -- 1800-1863 -- Correspondence; Smith, Francis Henney, -- 1812-1890 -- Correspondence; Tremlett, F. W. -- Correspondence; Werth, Mary, -- 1844-1928 -- Correspondence; Withers, Eliza, -- 1846- -- Correspondence; Morey family; Morey family -- Correspondence; Confederate States of America. -- Navy -- Officers; United States. -- Navy -- Officers; United States. -- Depot of Charts and Instruments; United States Naval Observatory; American Confederate voluntary exiles -- Mexico; Diplomatic and consular service, Confederate -- Great Britain; Meteorology; Mines and mineral resources; Oceanography; Physical geography -- Virginia; Science -- History -- 19th century; Torpedoes; Confederate States of America -- Foreign relations -- Great Britain; Confederate States of America -- History, Naval; Great Britain -- Foreign relations -- Confederate States of America; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History -- Civil War, 1861-1865 -- Refugees; Naval officers; Naval officers, Confederate; Oceanographers